Efek Pemanasan Pra-Kompaksi dan Sinter Terhadap Sifat Kuat Tekan Komposit Al/SiC: Mashuri dan I. Mufidah - Mashuri Mashuri; I. Mufidah I. Mufidah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
Research on the effects of pre-compacting heating on Aluminum (Al) matrix and sintering on the density and compressive strength of Al/SiC composites made using powder metallurgy method. The synthesized of Al/SiC composites was began by heating pre-compacting of Al matrix at temperatures of 40, 60, and 800 C within 1 hour, mechanically compacting and sintering at temperatures of 400, 500, and 6000 C. In order to increase the homogeneity of pressure during compacting throughout in the composites, non-reactive and volatile zinc stearate was used. Phase and morphological identification were carried out using X-rays Diffractometry (XRD) and Scanning Electron Microscope (SEM) devices. The density and porosity were measured by the Archimedes method and the compressive strength was tested by the Torsee Universal Testing Machine. The results showed that pre-compacting in the Al matrix with the temperature of 600 C and sintered temperatures up to 5000 C can increase the density and the compressive strength of Al/SiC composites prepared by powder metallurgy method. Sintering process can give a new phase -Al2O3 in the surface area contact of Al-SiC which can strengthen interfacial bonds and reduce porosity so that the density and the compressive strength increase.